Benchmark calculations of ro-vibrational spectrum of HeH− and its isotopologues. (22nd October 2020) - Palikot, Ewa; Stanke, Monika; Adamowicz, Ludwik
Abstract: Benchmark variational calculations of the Born–Oppenheimer potential energy curve (PEC) performed with explicitly correlated all-electron Gaussian functions with shifted centers are presented. The PEC energies include the leading relativistic and quantum-electrodynamics corrections and the first-order corrections due to adiabatic effects. The PEC is used to calculate the ro-vibrational spectra for HeH − and its isotopologues. The results show that these systems are marginally stable and have two to four bound vibrational levels and, for each vibrational level, a few bound rotational levels lying below the dissociation threshold. This indicates a possibility of detecting the HeH − anion in the laboratory and, perhaps, even in the interstellar space.